State constrained hybrid vehicle optimal energy management: an interior penalty approach. Issue 1 (July 2017) - Kareemulla, T.; Delprat, S.; Czelecz, L.
Abstract: In simulation, hybrid vehicle energy management can be formulated as a state constrained optimal control problem. Pontryagin's Minimum Principle provides necessary optimality conditions. Due to the state constraints, these conditions are non-solvable without any additional information about the solution structure. The proposed approach is to approximate the initial problem by replacing the formal state constraints by penalty terms. As a result, using Pontryagin's Minimum Principle, a Boundary Value Problem is obtained and two continuation procedures are proposed to numerically derive its solution.